First record of Plocama brevifolia in Europe (province of Cadiz, Spain) with taxonomic and ecological remarks - Muñoz-Secilla, Felipe; Vega-Pérez, Alberto; Devesa, Juan A.; Martínez Sagarra, Gloria (Mediterranean Botany, 2025)
We report the presence of Plocama brevifolia (Rubiaceae) in the southwest of the Iberian Peninsula (province of Cadiz, Spain). This discovery is not only the first record of the species in the Iberian Peninsula, but also in Europe. We provide ecological notes focusing on the conservation risks associated with this area. Some taxonomic remarks are also included based on a review of North African herbarium specimens.